Climate‐forced changes in available energy and methane bubbling from subarctic lakes. Issue 6 (30th March 2015) - Thornton, Brett F.; Wik, Martin; Crill, Patrick M.
Abstract: Strong correlations between seasonal energy input and methane (CH4 ) bubbling (ebullition) in northern lakes suggest that energy proxies might provide a constraint on the magnitude of future CH4 emissions. Ebullition is a major pathway for transporting anaerobically produced CH4 from lake sediments to the atmosphere and represents a large unquantified CH4 source. In high‐latitude, postglacial lakes during the ice‐free season, solar shortwave energy input can constrain CH4 productivity via control of sediment temperature. Utilizing long‐term climatic predictors, we calculate CH4 ebullition from three subarctic lakes in northern Sweden over the period of 1916–2079. Using observed energy trends, the seasonal average lake CH4 ebullition is predicted to increase by 80% between the 1916–1926 decade and the 2040–2079 period. Present‐day seasonal average methane ebullition is estimated to have already increased 24% since the 1916–1926 decade. Key Points: Expanded data set reinforces strong energy‐CH4 ebullition link in subarctic lakes Twenty eight years of shortwave energy measurements used to estimate past CH4 ebullition Study lake CH4 ebullition increases 80% between years 1916–1926 and 2040–2079